PROBLEMATIKA PEMBANGUNAN PARIWISATA BUDAYA DI DESA PULAU MARINGKIK - Putraji, Lalu Muhammad Guguh; Furkan, Lalu Muhammad; Uswanti, Bimantari Putri; Wandikbo, Indikum Nyamuk; Fadli, Muhammad; Zubaidi, Mayoni; Estiana, Elsa; Jumiarti, Jumiarti; Alivia, Fajri Atullah; Olvyana, Annsia; Ardiansyah, Ardiansyah; Asry, Nur (Jurnal Wicara, 2023)
Cultural tourism or "cultural tourism" in Maringkik as one of the strategies to reduce regional and economic development inequality, where this tourism is managed by community groups that collaborate with the government, as well as institutions outside the government. Community-based social tourism can be a tool for nature conservation and reducing cultural assimilation. This research is an activity that focuses on examining and analyzing the traditions and culture of the Maringkik people from the perspective of community tourism development. This problem is studied with the aim of increasing the knowledge of the Maringkik community regarding the management of tourism potential and its contribution to the development of new knowledge on alternative forms of tourism. The method used in this study is descriptive qualitative using a participant approach, where data collection uses surveys and qualitative methods. The survey was conducted by means of interviews with the community and village structures of Maringkik Island using the old method. The data is tabulated and processed then described. To evaluate the characteristics of â€œcultural tourismâ€, a survey is designed for tourism facility providers that will be formed by the community and providers. A survey was also conducted to determine the population and economic level of the community. With surveys and qualitative studies, data related to the potential for traditional and cultural tourism owned by the Maringkik people can be mapped quite comprehensively. The results of this study are that the tourism potential in Maringkik is related to two things, firstly discovering the traditions and culture of the local community, secondly, the tourism potential in Maringkik cannot be separated from the beach and the gills.